The Study of Adjustment of PBJT Parking Service Tariffs Due to the Implementation of Law Number 2 of 2024 Concerning the Special Region of Jakarta: Policy Analysis and Its Implications - Kadirisman, Indra; Dianari, Wahyu; Mustika, Febri Yoga; Perdana, Bayu Putra; Prawitra, Devry; Widyasa, Metryana (Monas: Jurnal Inovasi Aparatur, 2025)
This academic study examines the adjustment of the Specific Goods and Services Tax (PBJT) tariff on parking services in Jakarta, grounded in Law No. 2 of 2024, which authorizes DKI Jakarta to set parking tax rates up to 25%. The policy aims to alleviate traffic congestion, optimize parking utilization, and increase local revenue (PAD). Through qualitative analysis, including document reviews and stakeholder interviews, this study evaluates the policy’s legal framework, economic and social impacts, and its potential to improve traffic management. Findings suggest that tariff adjustments could discourage private vehicle use and encourage public transport adoption, contributing to reduced congestion and environmental improvement. However, the impact on lower-income groups calls for a balanced policy approach and compensatory measures. The study provides recommendations for policy design to maximize social benefits and support sustainable urban management in Jakarta.